Sosialisasi Aplikasi Among Tani oleh Dinas Pertanian dan Ketahanan Pangan untuk Mewujudkan Kota Batu sebagai Smart City - Nonny Lavka Vanya; Maman Suherman (UNISBA Press, 2022)
Abstract. This research is related to the concept of smart city or smart city. In the thesis that is studied, it is related to the Socialization of the Among Tani Application to Realize a Smart City. Is this socialization going well and being realized for people who work as farmers? The purpose of this study was to determine the strategy of the Department of Agriculture in disseminating to farmers the Among Tani application in Batu City. In the focus of research carried out in depth and clearly, this study uses descriptive qualitative methods to provide facts and data regarding the strategy of the Batu City Government in data management, and increase awareness of the use of applications in agriculture for the community, especially farmers, then the data is analyzed using brand awareness theory and new media theory. The socialization activity of the Among Tani application by the Department of Agriculture and Food Security of Batu City with farmer groups was carried out in 2018-2019. In increasing the awareness of farmers, it is important to provide education on the use of IT in Batu City. The results of this study stated that the Batu City Government, namely the Batu City Agriculture and Food Security Service through the counseling team, farmer assistant staff and the crop team carried out socialization in several stages, namely: planning stage 1) initial community research in Batu city; 2) coordination meeting in order to the declaration of BATT; 3) recruitment plan for companion team, extension team and crop team; 4) providing materials to the team that has been formed for socialization. Batu city government makes plans for socialization activities. The implementation stage, namely . The implementation phase of the Among Tani application socialization activity is the distribution of leaflets or brochures, and launching an extension team to meet face-to-face with farmer groups or communities that are the targets of this socialization. The evaluation and reporting stages are carried out after the socialization activities have been running. The use of media to support the process of socialization activities, namely audio-visual media and social media, namely Instagram, Twitter, Facebook and YouTube. Then by using electronic media supported by leaflets and SMS gateway. The delivery of messages is first, the socialization is carried out to convey the implementation of using the Among Tani application in 2017 and is actively realized until 2019. Second, Explaining the use of the Among Tani application which is a smart city program in Batu City. Abstrak. Penelitian ini berkaitan dengan konsep smart city atau kota cerdas. Dalam skripsi yang dikaji berkaitan dengan Sosialisasi Aplikasi Among Tani untuk Mewujudkan Smart City. Apakah sosialisasi ini berjalan dengan baik dan terealisasikan kepada masyarakat yang berprofesi sebagai petani. Tujuan dalam penelitian ini adalah untuk mengetahui strategi Dinas Pertanian dalam mensosialisasikan kepada para petani terhadap aplikasi Among Tani Kota Batu. Dalam fokus penelitian dilakukan secara dalam dan jelas, penelitian ini menggunakan metode kualitatif deskriptif untuk memberikan fakta dan data mengenai strategi Pemerintah Kota Batu dalam pengelolaan data, dan meningkatkan kesadaran penggunaan aplikasi dalam bidang pertanian untuk masyarakat terutama petani, kemudian data dianalisis menggunakan teori brand awareness dan teori new media. Kegiatan sosialisasi aplikasi Among Tani oleh Dinas Pertanian dan Ketahanan Pangan Kota Batu dengan kelompok tani dilakukan pada tahun 2018-2019. Dalam meningkatkan kesadaran para petani diberikannya edukasi penting penggunaan IT di Kota Batu. Hasil penelitian ini menyatakan bahwa Pemerintah Kota Batu yaitu Dinas Pertanian dan Ketahanan Pangan Kota Batu melalui tim penyluhan, tenaga pendamping petani serta tim crop melakukan sosialisasi dengan beberapa tahapan yaitu : tahap perencanaan 1) riset awal masyarakat di kota Batu ;2) rapat koordinasi dalam rangka pencanangan BATT; 3) rencana perekrutan tim pendamping, tim penyuluh dan tim crop; 4) pembekalan materi pada tim yang telah dibentuk untuk sosialisasi., pemerintah kota batu membuat perencanaan untuk kegiatan sosialisasi. Tahap pelaksanaan, yaitu . Tahap pelaksanaan dari kegiatan sosialisasi aplikasi Among Tani yaitu penyebaran leaflet atau brosur, serta meluncurkan tim penyuluhan untuk bertatap muka langsung dengan kelompok atau komunitas tani yang menjadi sasaran dari sosialisasi ini. Tahap evaluasi dan tahap pelaporan, dilakukan setelah kegiatan sosialisasi sudah berjalan. Penggunaan media untuk medukung proses kegiatan sosialisasi yaitu media audio visual serta media sosial yaitu Instagram,twitter, facebook dan youtube. Lalu dengan menggunakan media eketronik didukung dengan leaflet serta SMS gateaway. Penyampaian pesan yaitu pertama, Sosialisasi dilakukan untuk menyampaikan pemberlakuan dalam menggunakan aplikasi Among Tani ditahun 2017 dan terealisasikan secara aktif hingga tahun 2019. Kedua, Menjelaskan penggunaan aplikasi Among Tani yang merupakan program smart city Kota Batu.